The Effect of Taxes on Corporate Financing Decision - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)

How sales strategy translates into performance: The role of salesperson customer orientation and value-based selling - Terho, Harri; Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang (Industrial Marketing Management)

Heading for new shores: Do service and hybrid innovations outperform product innovations in industrial companies? - Eggert, Andreas; Thiesbrummel, Christoph; Deutscher, Christian (Industrial Marketing Management)

"...and they are really lying: Clean Evidence on the Pervasiveness of Cheating in Professional Contexts from a Field Experiment" - Djawadi, Behnud Mir; Fahr, René (Journal of Economic Psychology)

Robust Equilibria in Location Games - Buechel, Berno; Röhl, Nils (European Journal of Operational Research)
In the framework of spatial competition, two or more players strategically choose a locationin order to attract consumers. It is assumed standardly that consumers with the same favorite location fully agree on the ranking of all possible locations. To investigate the necessity of this questionable and restrictive assumption, we model heterogeneity in consumers’ distance perceptions by individual edge lengths of a given graph. A proﬁle of location choices is called a “robust equilibrium” if it is a Nash equilibrium in several games which diﬀer only by the consumers’ perceptions of distances. For a ﬁnite number of players and any distribution of consumers, we provide a full characterization of all robust equilibria and derive structural conditions for their existence. Furthermore, we discuss whether the classical observations of minimal diﬀerentiation and ineﬃciency are robust phenomena. Thereby, we ﬁnd strong support for an old conjecture that in equilibrium ﬁrms form local clusters.

Wertbasiertes Verkaufen auf Industriegütermärkten - Eggert, Andreas; Haas, Alexander; Ulaga, Wolfgang; Terho, Harri (Handbuch Business-to-Business-Marketing)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Instructional Design of Mobilities in Vocational Education - Background, Concepts and Experiences

Kurzportrait zum Standortkonzept des Berufskollegs West der Stadt Essen - Frehe, Petra; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

„Career Planning for dynamic Economies" – Individualisierung und Neue Medien als Anknüpfungspunkt für berufliche Orientierung im Rahmen des EU geförderten Projekts SELFIE - Beutner, Marc; Rose, S (Wirtschaft und Erziehung)

Open Educational Resources in der aktuellen Bildungslandschaft: Motivation zur Teilung und Nutzung - Beutner, Marc; Schneider, J. N. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Förderung von Berufsorientierung, Basiskompetenzen und Ausbildungsreife als Herausforderung von Bildungsgangarbeit in Bildungsgängen der beruflichen Grundbildung - Beutner, Marc; Rose, S (Individuelle Kompetenzentwicklungswege – Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Medienkompetenz im Kontext beruflicher Orientierung - Beutner, Marc; Rose, M (Individuelle Kompetenzentwicklungswege – Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Gewaltprävention als Herausforderung für die Bildungsgangarbeit - Beutner, Marc; Rohde, S (Individuelle Kompetenzentwicklungswege – Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Relevanz der Zinsschranke – eine empirische Untersuchung der betroffenen Unternehmen von 2008 bis 2012 - Alberternst, Stephan; Schwar, Torben

Die Besteuerung von Personengesellschaften unter besonderer Berücksichtigung der Verlustnutzungskonzeptionen und Gewinnverwendungsoptionen - Eine Analyse der Wechselwirkungen zwischen § 10d, § 15a, § 32a und § 34a EStG - Rickermann, Anja

Mehr Theorie wagen: Eine neue Ausbildung für die Praxis? - Sureth, Caren (WiSt - Wirtschaftswissenschaftliches Studium)